2020
DOI: 10.1186/s12961-020-0527-x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Athena SWAN award scheme for gender equality as a complex social intervention in a complex system: analysis of Silver award action plans in a comparative European perspective

Abstract: Background: Given the complex mix of structural, cultural and institutional factors that produce barriers for women in science, an equally complex intervention is required to understand and address them. The Athena SWAN Award Scheme for Gender Equality has become a widespread means to address barriers for women's advancement and leadership in the United Kingdom, Ireland, Australia, the United States of America and Canada, while the European Commission is exploring the introduction of a similar award scheme acr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 55 publications
2
42
0
Order By: Relevance
“…Our study compliments the existing literature on gender equity in universities by contributing a context-specific perspective on NIHR BRCs—partnerships between universities and NHS organisations. In doing so, our study contributes to the growing body of literature recognising the complexity of factors producing gender inequality and the importance of context-specific interventions for different categories of staff [ 36 – 40 ] Under the complexity approach, addressing gender inequality requires multiple areas of intervention with a focus on the local context and dynamics [ 40 – 42 ]. Therefore, context-specific GE markers can help to identify areas for improvement, plan interventions, and monitor progress against the goals and strategic objectives for different categories of staff.…”
Section: Discussionmentioning
confidence: 99%
“…Our study compliments the existing literature on gender equity in universities by contributing a context-specific perspective on NIHR BRCs—partnerships between universities and NHS organisations. In doing so, our study contributes to the growing body of literature recognising the complexity of factors producing gender inequality and the importance of context-specific interventions for different categories of staff [ 36 – 40 ] Under the complexity approach, addressing gender inequality requires multiple areas of intervention with a focus on the local context and dynamics [ 40 – 42 ]. Therefore, context-specific GE markers can help to identify areas for improvement, plan interventions, and monitor progress against the goals and strategic objectives for different categories of staff.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulties of managing large multidisciplinary KT teams that include sex and gender experts as well as patients and other stakeholders is related to the complexity of managing a vast array of perspectives and representing everyone’s interests equally. This is confirmed in a study comparing the Athena SWAN award scheme with other gender equality initiatives in Europe, which found that interventions are complex social interventions in a complex system [ 29 ]. A multitude of contextual variables relate in complex, non-linear ways and must constantly adapt to moving targets and new conditions.…”
Section: Discussionmentioning
confidence: 68%
“…The contribution of ADVANCE to increasing inclusivity has been difficult to separate from overall institutional and academic pushes for inclusivity; additionally, their projects include small numbers of individuals and multiple interventions, which makes it difficult to isolate change [ 11 ]. The Athena SWAN project also found it difficult to directly link the effects of policy changes with their initiatives [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Articles on the main components of a NHRS were supplemented by some important papers on topics that are highly relevant but which feature less frequently in HARPS. These include a study aimed at reducing the research waste that arises from disproportionate regulation by examining the practices for exempting low-risk research from ethics review in four high-income countries [71], the Global Observatory's paper on research funding described earlier [29], a study on the governance of national health research funding institutions [72], and one on a more recent topic of growing significancean analysis of attempts to boost gender equality in health research [73]. Additionally, some of the papers on specific components, such as impact evaluation or use of evidence, are extending the analysis.…”
Section: Whose Literature?mentioning
confidence: 99%